1, 2‐Disubstituted 3, 3, 4, 4, 5, 5‐Hexafluorocyclopentenes as Bent Light‐Emitting π‐Conjugated Luminophores. Issue 7 (12th February 2020) - Yamada, Shigeyuki; Nishizawa, Akito; Agou, Tomohiro; Kubota, Toshio; Konno, Tsutomu
Abstract : Herein, a series of 1, 2‐disubstituted 3, 3, 4, 4, 5, 5‐hexafluorocyclopentene derivatives is synthesized from the commercially available octafluorocyclopentene via addition‐elimination reactions, and their photophysical properties are investigated in detail. 1, 2‐Bis[2‐(4‐alkoxyaryl)ethyn‐1‐yl]‐3, 3, 4, 4, 5, 5‐hexafluorocyclopentene exhibits UV‐absorption at 345 nm in CH2 Cl2 and deep blue photoluminescence (PL). The PL properties of these derivatives, including color and maximum wavelength ( λ PL ), are strongly affected by the electron‐density distribution induced by the electronic characteristics of the alkoxy‐substituents at the 4‐position of the benzene ring, with more electron‐donating substituents resulting in a larger shift of λ PL to longer wavelengths. Note that the present light‐emitting π‐conjugated luminophores also exhibit relatively strong PL in the crystalline state, where λ PL shifts can be introduced by modulation of the terminal alkoxy‐chain length, resulting in different PL colors from light‐blue to orange. Abstract : 1, 2‐Disubstituted 3, 3, 4, 4, 5, 5‐hexafluorocyclopentenes, as synthesized from octafluorocyclopentene, show interesting photophysical properties. Using theoretical calculations and XRD measurements, the PL was found to be strongly affected by the electron‐density distribution as well as molecular aggregation.